A study on the preferences to contribute in Takaful scheme among non-muslims / Nuradlina Aliah Nor Azman. - Nor Azman, Nuradlina Aliah (2019)
Takaful, which is known among Muslims, is a system whereby participants contribute regularly to a common fund and intend to jointly guarantee each other, example to compensate any of the participants who inflicted with a specific risk. There is also conventional insurance that provides protection, but it is not based on shariah compliance. Majority of individuals purchase insurance rather than takaful. On the other hand, some of the non-Muslims choose takaful as their protection instead of conventional insurance. This research study aims to identify the concept of takaful as a universal protection and the factors that influence non-Muslims to choose takaful scheme as their protection. This research is based on data obtained from qualitative method which is field research, through in-depth interviews with the industry player and academician to achieve the objective of this study. This study has determined that takaful is suitable for all humans, regardless of religion and race. The awareness of the participants and the roles of agent are identified factors that influencing the non-Muslims to contribute in takaful.